Behavioral, not self-reported, experiential avoidance predicts early treatment discontinuation at residential substance use treatment - Wang, Wenyue; McChargue, Dennis E.; Khan, Bilal; Oakland, Andrew P. (Frontiers in Psychiatry, 2026)
ObjectivesA large proportion of unhoused individuals in residential substance use treatment discontinue treatment, though a longer stay in treatment consistently predicts successful recovery. Experiential avoidance (EA) as an important function underlying dysregulated emotions may contribute to negative treatment outcomes. Limited evidence is available for the effect of EA in predicting treatment discontinuation. The current study aimed to investigate the roles of both behavioral and self-reported EA in predicting early treatment discontinuation among unhoused individuals receiving residential substance use treatment.MethodFifty-five male participants were recruited from a residential treatment facility. Upon admission, participants rated their EA using the Acceptance and Action Questionnaire (AAQ) and completed a word-based Algebra Avoidance Task, with EA being indexed by premature termination of the task. Participants’ treatment completion status and days spent in treatment were obtained upon discharge. Cox proportional hazards regression analyses were conducted to predict time until treatment discontinuation, controlling for age, years of education, and psychological distress.ResultsResults suggest a significant effect of behavioral, but not self-reported, EA in predicting early treatment discontinuation, such that greater behavioral EA was associated with an increased hazard of early treatment discontinuation, HR = 2.50, 95% CI [1.09, 5.73], p = .030. Participants with a primary alcohol (versus non-alcohol substance) use disorder diagnosis were less likely to have demonstrated behavioral EA.ConclusionsBehavioral measures might provide a more proximal measure of EA than self-report. Treating EA may help improve treatment retention. More research is needed to extend the current findings and clarify the mechanisms.